Ligand-induced signal transduction within heterodimeric GABA(B) receptor - Margeta-Mitrovic, Marta (The National Academy of Sciences, 2001)
γ-aminobutyric acid type B (GABA(B)) receptors, G protein-coupled receptors (GPCRs) for GABA, are obligate heterodimers of two homologous subunits, GB1 and GB2. Typical for family C GPCRs, the N termini of both GB1 and GB2 contain a domain with homology to bacterial periplasmic amino acid-binding proteins (PBPs), but only the GB1 PBP-like domain binds GABA. We found that both GB1 and GB2 extracellular N termini are required for normal coupling of GABA(B) receptors to their physiological effectors, G(i) and G protein-activated K(+) channels (GIRKs). Receptors with two GB2 N termini did not respond to GABA, whereas receptors with two GB1 N termini showed increased basal activity and responded to GABA with inhibition, rather than activation, of GIRK channels. This GABA-induced GIRK current inhibition depended on GABA binding to the chimeric GB(1/2) subunit (the GB1 N-terminal domain attached to the heptahelical domain of GB2), rather than the wild-type GB1 subunit. Interestingly, receptors with reciprocal exchange of N-terminal domains between the subunits were functionally indistinguishable from wild-type receptors. We also found that peptide linkers between GB1 and GB2 PBP-like domains and respective heptahelical domains could be altered without affecting receptor function. This finding suggests that other contacts between the PBP-like and heptahelical domains underlie ligand-induced signal transduction, a finding likely to be relevant for all family C GPCRs.